A rare cause of sudden chest pain and dyspnea: A CARE-compliant case report of Chilaiditi syndrome. Issue 20 (15th May 2020) - Xu, Yanling; Wang, Qi; Meng, Guangping; Li, Dapeng; Ma, Zhiming; Gao, Peng; Zhang, Jie; Zhang, Qun; Su, Zhenzhong
Abstract: Rationale: Chilaiditi syndrome is a rare disorder characterized by a broad spectrum of (gastro-intestinal) symptoms caused by interposition of a segment of bowel between the liver and the diaphragm. Most cases present with abdominal symptoms and the morbidity tend to increase with age. Patient concerns: Here we present a rare case of Chilaiditi syndrome. An elderly postmenopausal woman developed unresolved postoperative respiratory symptoms and chest pain. Chest auscultation revealed considerable attenuation of respiratory sounds. She showed postoperative increase in D-dimer level and sudden onset of dyspnea. Diagnoses: Considering the presence of atelectasis in the middle and lower lobes of the right lung, bedside fiberoptic bronchoscopy was performed immediately to rule out bronchial phlegm embolism. However, no phlegm embolism was found in the left lung, and a small amount of yellow–white mucus was seen in the upper lobe of the right lung. Due to external pressure, the lumen of the middle and lower lobes of the right lung was obviously narrowed. Interventions: The patient was placed in a semi-sitting position and a tube was passed through the anus to decompress the intestinal cavity; in addition, she received potassium supplementation. Outcomes: The patient's symptoms improved markedly. Chest and semi-supine abdominal plain radiographs showed enhanced lung markings, shadows in the left lower lung lobes, elevation of the right diaphragm, and small amount of pneumoperitoneum. The patient recovered after 5 days of continuous treatment and was discharged. Lessons: Emergency computed tomographic pulmonary angiography may facilitate the diagnosis of Chilaiditi syndrome, especially in the postoperative setting. Occurrence of Chilaiditi syndrome in this patient was likely associated with surgical factors. Appropriate investigations and clear identification of etiology are essential for successful treatment.